Breaking Barriers: Research and Development of Infinity Vocabulary Game App to Improve English Vocabulary of Fifth Graders - Kristanto, Yenny; Tambunan, Aripin; Winardi, Yonathan (research, training and philanthropy institution Natural Aceh, 2024)
Learning English at the primary school level holds significant relevance in preparing students to face global challenges in the future. Appropriate technology can support English language Learning, allowing students to experience maximum development. This research elaborates on developing and utilizing the Infinity Vocabulary Game App, which is tailored to meet the needs and enhance the English vocabulary of grade 5 students in Tangerang. The study utilized the ADDIE model, which covered analysis, design, development, implementation, and evaluation, along with a quantitative experimental approach. A pretest-posttest design was applied involving 66 participants of grade 5 students from SDN Sewan Kebon, divided into an experimental group (28 students), a control group (28 students), and a small-scale test group (10 students). Data collection tools, including observations, interviews, rubrics, questionnaires, and the Infinity game application, have been validated by experts. The N-Gain test showed a high effectiveness score of 0.72. The Mann-Whitney test revealed significant differences in average scores between the experimental and control groups. The research indicated that the Infinity game application was efficient and significantly improved students' English vocabulary. Furthermore, the students experienced high satisfaction and motivation when using the Infinity game application.